GOOD GOVERNANCE DALAM KONFIGURASI NEGARA KESEJAHTERAAN VERSI 1945: TINJAUAN KRITIS TATA KELOLA PEMERINTAHAN DAERAH DI INDONESIA - Saidi, Anas (Jurnal Masyarakat dan Budaya, 2011)
The implementation of good governance is very popular since the successful implementation of local government autonomy inIndonesia. Efficiency, effectivity, accountability, transparency, and participation, as the key principles in the application of good governance have been successful in lessening the emerging bad governance that in the past had been the prime character of Indonesian bureaucracy. The suggestion to the need of mindsetchanges of government system to apply bureaucracy entrepreneurship principles have been the only paradigm in the governance of local government in Indonesia. The overstated spirit in supporting those principles makes us easily address critical question on whether good governance is not merely as a tool of a neutral ideological interest. Is there any possibility for good governance to have hidden agenda that finally place market as the main source of chance contradictory to welfare state principles as stated in Indonesian Constitution of 1945; or whether good governance is a need for transition period that can be utilized as a step to achieve welfare state. This writing is aimed at addressing critical review on: how the good governance that has many positive results can be utilized as the main referenced in running the government in reform era, that is contrary to the principles of welfare state version in the Indonesian Constitution of 1945. If the hypothesis of there is ideologically-significant difference between good governance and welfare state is true, then at least there is a need for responding critically the journey of good governance in gaining its final purpose. In other words, there is a need of rethinking or reviewing the hegemony of mindset in the whole stakeholders, which is believed as the only way to gain people welfare. The question then do we capable of redesigning good governance which has final purpose to gain welfare state principles as dreamed by Indonesian Constitution of 1945.Keywords: good governance, welfare state, governance of local government.